2015
DOI: 10.2807/1560-7917.es2015.20.19.21127
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence in blood donors reveals widespread, multi-source exposure to hepatitis E virus, southern France, October 2011

Abstract: The apparent seroprevalence of hepatitis E Virus (HEV) varies greatly among developed countries depending on the geographical area and the sensitivity of immunoassays. We used a validated assay to determine the prevalence of HEV IgG and IgM antibodies among 3,353 blood donors living in southern France, who gave blood during the two first weeks of October 2011 and participated in the study. Demographic and epidemiological information was collected using a specific questionnaire. We also screened 591 samples for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 30 publications
6
51
1
Order By: Relevance
“…87 In a study of blood donors exposed to HEV infection in Southern France, foodstuffs associated with positive antibodies against HEV on multivariate analysis were uncooked pork liver sausages, offal and mussels. 73 To support this, HEV has been found to be highly prevalent amongst global pig populations. For example, in Germany, 33% of wild boar and 50% of domestic pigs are seropositive for anti-HEV IgG.…”
Section: Genotypementioning
confidence: 99%
“…87 In a study of blood donors exposed to HEV infection in Southern France, foodstuffs associated with positive antibodies against HEV on multivariate analysis were uncooked pork liver sausages, offal and mussels. 73 To support this, HEV has been found to be highly prevalent amongst global pig populations. For example, in Germany, 33% of wild boar and 50% of domestic pigs are seropositive for anti-HEV IgG.…”
Section: Genotypementioning
confidence: 99%
“…However, the detection of HEV antibodies provides useful information on the immune status or stages of HEV infection in blood donors and may assist with the identification of risk factors for exposure. Seroprevalence is also important for assessing the overall disease burden in a population, and studies have shown that HEV exposure in blood donors varies widely between geographical regions [18, 19]. For example, 6% of Australian blood donors have been shown to be HEV IgG positive, while 52% of donors in southwestern France were HEV IgG positive with the same assay [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Although the cause of this (re)emergence of HEV is unknown, one hypothesis is that dietary habits and contaminated water have both contributed to the increased incidence of HEV in this population. (25) Thus, the proportion of the general population harboring protective immunity to HEV and the way it evolves differ from one country to another and probably even between areas within the same country.…”
Section: Mansuy Gallian Et Al Hepatology April 2016mentioning
confidence: 99%
“…These HEV genotypes have been detected in a wide range of domestic and wild animals, which are believed to play a major role in the human epidemiology of the virus. (2) HEV genotypes 1 and 2 mainly affect young adults, mostly men, aged [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Almost half of all cases become jaundiced, and pregnant women during the third trimester and patients with underlying chronic liver disease are most at risk of a severe form of hepatitis E. (3) HEV genotypes 3 and 4 mainly affect older men.…”
mentioning
confidence: 99%